Penerimaan Teknologi Artificial Intelligence (AI) di Proses Rekrutmen dan Seleksi Oleh Pelamar Kerja - Putro, Muhammad; Siswanto , Joko (Journal of Research in Industrial Engineering and Management, 2025)
The use of technology in the recruitment and selection process has evolved alongside organizational competition to identify, select, and retain top talent. Artificial Intelligence (AI) technology in recruitment and selection offers various advantages from an organizational perspective. However, job applicants' perceptions of AI technology have been rarely discussed in the literature, even though this issue significantly impacts their attitudes and work behaviors after the recruitment and selection process. This study focuses on job applicants' acceptance of AI technology using theoretical models of technology acceptance to understand the factors influencing their intention to use AI. The PLS-SEM statistical method was used for data processing with SmartPLS software. Based on data from 166 respondents in Jabodetabek and Bandung who had never participated in AI-based recruitment and selection, the study found that perceived usefulness, perceived ease of use, and trust positively influence the intention to use AI, with attitude acting as a mediator. Perceived usefulness and perceived ease of use also have a direct positive effect. Additionally, attitude and social influence positively affect the intention to use AI. However, perceived knowledge does not have a significant impact on job applicants' intention to use AI in recruitment and selection.